2011
DOI: 10.1242/jcs.080853
|View full text |Cite
|
Sign up to set email alerts
|

‘White wave’ analysis of epithelial scratch wound healing reveals how cells mobilise back from the leading edge in a myosin-II-dependent fashion

Abstract: Collective cell migration is absolutely essential for a wide variety of physiological episodes including the re-epithelialisation component of tissue repair. However, the investigation of such processes has been frustrated by difficulties in quantitatively analysing the behaviours of a large body of cells within a migrating epithelial sheet, which previously required manually tracking a large number of individual cells, or using advanced computational techniques. Here, we describe a novel and simpler image sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 28 publications
10
38
0
Order By: Relevance
“…Basal epidermal cells behind the LE also formed cryptic lamellipodia (Fig. 2G, lower panel), as has been suggested previously from in vitro experiments (Matsubayashi et al, 2011). Only in rare cases did individual LE keratinocytes form lamellipodia that projected beyond the otherwise homogeneous lamellipodial front (Fig.…”
Section: Re-epithelialization Of Cutaneous Wounds Is Extremely Rapidsupporting
confidence: 85%
See 2 more Smart Citations
“…Basal epidermal cells behind the LE also formed cryptic lamellipodia (Fig. 2G, lower panel), as has been suggested previously from in vitro experiments (Matsubayashi et al, 2011). Only in rare cases did individual LE keratinocytes form lamellipodia that projected beyond the otherwise homogeneous lamellipodial front (Fig.…”
Section: Re-epithelialization Of Cutaneous Wounds Is Extremely Rapidsupporting
confidence: 85%
“…In cultured epithelial cells, closure of scratched wounds is not only achieved by activities at the front row, but also involves several rows of following epithelial cells that migrate as coherent cell sheets (Farooqui and Fenteany, 2005;Fenteany et al, 2000;Matsubayashi et al, 2011). We observed a similar phenomenon in keratinocytes following the LE in zebrafish wounds in vivo, with (cryptic) lamellipodia also formed by second and third row keratinocytes (Fig.…”
Section: Transgenic Inhibition Of Fgf Signalling Does Not Compromise supporting
confidence: 58%
See 1 more Smart Citation
“…Therefore, TC migration does not rely on actomyosin contractibility, posing the question: which molecular players might be involved in TC force generation? Interestingly, collective movement of cells depends on actin-based filopodia and lamellipodia (Mayor and Etienne-Manneville, 2016), and was shown in several cases to be independent of MyoII activity (Matsubayashi et al, 2011;SerraPicamal et al, 2012). Furthermore, several studies showed that a downregulation of MyoII is required for effective collective cell migration (Hidalgo-Carcedo et al, 2011;Omelchenko and Hall, 2012;Yamada and Nelson, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical scraping can be performed using a pipette tip, needle, bladder, razor, rubber policeman, cotton bud, or Teflon spatula for creating a single scratch or a plastic hair comb or wounder for creating multiple scratches simultaneously. [7][8][9][10][11][12][13] To standardize the process and increase the throughput, the scratching assay can be implemented using a robotic system. 14 To improve the reproducibility and minimize the surface damage, a drill press assay has been developed.…”
Section: Mechanical Wounding Assaymentioning
confidence: 99%